Condensed tannins are inducible antioxidants and protect hybrid poplar against oxidative stress. (27th March 2019) - Gourlay, Geraldine; Constabel, C Peter
Abstract: Condensed tannins (CTs) have been studied extensively as potential defenses against pests and pathogens, and for their beneficial effects on human health. They are known to possess high in vitro antioxidant capacity, but whether they can function as in planta antioxidants for protection against oxidative stress has not been previously tested. Here, we show that stress induction of CTs in poplar ( Populus ) is matched closely by an increase in antioxidant activity under both high light and nitrogen deficiency. We also investigate the effects of CTs as in vivo antioxidants directly, using transgenic poplar plants which overexpress poplar MYB transcription factors that regulate the CT pathway. These transgenics have 50-fold higher CT concentrations than controls, and and also have dramatically higher antioxidant activity. High-CT and control poplar leaves were exposed to methyl viologen for 24 h. Chlorophyll fluorescence was used to measure maximum quantum efficiency of photosystem II photochemistry ( Fv/Fm ), and leaf discs were stained with 3, 3′-diaminobenzidine (DAB) and nitroblue tetrazolium (NBT) to assess hydrogen peroxide and superoxide levels. After methyl viologen exposure, high-CT transgenics retained higher Fv/Fm ratios and accumulated less hydrogen peroxide and superoxide than the controls. Our findings indicate that high-CT concentrations protect poplar against methyl viologen-induced oxidative stress and suggest a broader function of CTs than previously supposed.